Early divergence of central and peripheral neural retina precursors during vertebrate eye development. Issue 3 (17th November 2014) - Venters, Sara J.; Mikawa, Takashi; Hyer, Jeanette; Trainor, Paul; Johnson, Randy
ABSTRACT Background: During development of the vertebrate eye, optic tissue is progressively compartmentalized into functionally distinct tissues. From the central to the peripheral optic cup, the original optic neuroepithelial tissue compartmentalizes, forming retina, ciliary body, and iris. The retina can be further sub‐divided into peripheral and central compartments, where the central domain is specialized for higher visual acuity, having a higher ratio and density of cone photoreceptors in most species. Results: Classically, models depict a segregation of the early optic cup into only two domains, neural and non‐neural. Recent studies, however, uncovered discrete precursors for central and peripheral retina in the optic vesicle, indicating that the neural retina cannot be considered as a single unit with homogeneous specification and development. Instead, central and peripheral retina may be subject to distinct developmental pathways that underlie their specialization. Conclusions: This review focuses on lineage relationships in the retina and revisits the historical context for segregation of central and peripheral retina precursors before overt eye morphogenesis. Developmental Dynamics 244:266–276, 2015. © 2014 Wiley Periodicals, Inc.